New insights into Lactocollybia (Agaricales, Basidiomycota): Morpho-phylogenetic analyses revealing two interesting species and one new record from Thailand and evidence of intercontinental conspecificity - Ishika Bera; Komsit Wisitrassameewong; Naritsada Thongklang (MycoKeys)
The genus Lactocollybia (incertae sedis, Agaricales) is a small and relatively understudied group of mushrooms, exhibiting unique morphological and ecological characteristics. Most species have a saprobic lifestyle, distributed in tropical to subtropical regions. Currently, the phylogenetic relationships of species remain poorly understood due to insufficient DNA sequence data of existing species. This study is an integrative approach, combining morphological characteristics and molecular analyses using nrITS and two-locus (nrITS-nrLSU) phylogenetic estimation. For the latter, we tested phylogenetic lineages of publicly available nrITS sequences and six samples from Thailand. Our phylogenies have revealed that Thai samples are placed in three phylogenetic clades, in which one of them is proposed as a new species, L. polyhabitata, whereas L. variicystis is reported for the first time from Thailand, suggesting a broader distribution of this species in the tropical region. Another species, L. cf. epia, has been critically analyzed for its affinity towards L. epia. All studied species are placed in phylogenetic clades with a multitude of collections from different continents, which suggests the evidence of intercontinental conspecificity across tropical and subtropical regions.